Solvability to a Second Order Multipoint Boundary Value Problem on a Half-Line - Khamsa ,Mouna; Nisse ,Aicha (Université of eloued جامعة الوادي, 2025)
In this memory, we have studied the existence of solutions to certain boundary value problems of second-order differential equations posed on unbounded intervals and associated with multi-point boundary conditions. Methods have been used to prove the existence of solutions. These methods are based on the study of the corresponding Green’s function and some of its properties. We have transformed the differential equation into an operational equation. Using a fixed point theorem, sufficient conditions are obtained guaranteeing the existence of at least one solution. Some examples illustrate the applicability of our main results. Dans ce mémoire, nous avons étudié l’existence des solutions à certains problèmes aux limites d’équations différentielles du second ordre posées sur des intervalles non bornés et associées à des conditions aux limites à multi points. Des méthodes ont été employées pour prouver l’existence des solutions. Ces méthodes reposent sur l’étude de la fonction de Green correspondante et de certaines de ses propriétés. Nous avons transformé l’équation différentielle en équation opérationnelle. Grâce à un théorème du point fixe, des conditions suffisantes sont obtenues garantissant l’existence d’au moins une solution. Quelques exemples illustrent l’applicabilité de nos principaux résultats.
Fundamental and Applied Mathematics
Keywords: Differential equation; existence; multipoint; boundary value problem; infinite interval; fixed point theorem.; Équation différentielle; problème aux limites; intervalle infini; théorème du point fixe.